1977
DOI: 10.1021/ja00467a030
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic peptides. 19. Cation binding of a cyclic dodecapeptide cyclo (L-Val-Gly-Gly-L-Pro)3 in an aprotic medium

Abstract: The synthesis of cyclo-(~-Val-Gly-Gly-~-Pro)3 is reported. This homodetic cyclic dodecapeptide contains only naturally occurring amino acids and is a model of an ion carrier related to valinomycin. Titration curves obtained from circular dichroism data in acetonitrile solutions reveal three kinds of cyclic dodecapeptide (P)-cation (C) complexes: PC (1:l complex), P2C (peptide-sandwich complex), and PC2 (ion-sandwich complex). Binding constants of several cations and molar ellipticities of the bound species wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Another synthetic analogue of valinomycin, cyclo(L-Va1-Gly-Gly-~-Pro)~ [cycl~(VGGP)~l,' synthesized in our laboratory (Pease, 1975; Baron et a]., 1977), has been investigated using 'H and I3C N M R spectroscopy. In this compound Gly residues replace the two D residues of valinomycin, which may result in greater conformational freedom for the molecule.…”
Section: Cyclo(l-val-d-pro-d-val-l-pro)3mentioning
confidence: 99%
See 1 more Smart Citation
“…Another synthetic analogue of valinomycin, cyclo(L-Va1-Gly-Gly-~-Pro)~ [cycl~(VGGP)~l,' synthesized in our laboratory (Pease, 1975; Baron et a]., 1977), has been investigated using 'H and I3C N M R spectroscopy. In this compound Gly residues replace the two D residues of valinomycin, which may result in greater conformational freedom for the molecule.…”
Section: Cyclo(l-val-d-pro-d-val-l-pro)3mentioning
confidence: 99%
“…The decreased number of bulky side chains in this cyclic peptide relative to valinomycin and the earlier analogue may be expected to lead to greater access of complexed ions to solvent. An investigation of C J~~( V G G P )~, using circular dichroism (Baron et al, 1977), showed that this peptide forms stable complexes with alkali metal and alkaline earth metals and that the stabilities of the complexes are affected by both size and charges of the cations. It was shown that large cations (K', Ca*+, and Ba") form the most stable 1:l peptide-cation complexes and that of these the divalent ions bind more strongly by a large factor.…”
Section: Cyclo(l-val-d-pro-d-val-l-pro)3mentioning
confidence: 99%
“…36) In the most extended circular form, the outside diameter of the space-filling model of valinomycin molecule is about 3.14 nm 2 •24) When the close-packing state of valinomycin is in a two-dimensional hexagonal lattice, the occupied area is estimated at 3.46 nm 2 . In Fig.…”
Section: Temperature-dependence Of Gramicidin A' and Valinomycin Monomentioning
confidence: 99%
“…7 Reagent grade perchlorates dried in vacuo at 120°C were used as alkali and alkaline earth metal salts. 2 Spectrometric grade acetonitrile (DOJINDO Laboratories) was used as the solvent for CD measurement without further purification. CD spectra were recorded on a Jasco J-500A automatic recording spectropolarimeter equipped with a DP-500 data processor.…”
Section: Experiments Almentioning
confidence: 99%